The Effects of The Influence of Climatic Factors on The Average Yields of Wheat Varieties. An Evaluation in The Brăila Experimental Field, Romania - Emanuela Lungu; Maria-Magdalena Turek-Rahoveanu (Communications of International Proceedings, 2022)
Knowledge of natural resource management in quantitative terms is particularly valuable when talking about their sustainable use. The objective of the paper is to present the relationship between the pedoclimatic resources in South-East Romania and the zoning of wheat varieties in order to obtain higher quantitative and qualitative productions. The studies were carried out over a period of 10 years, tracking the influence of climate change on the productions of the varieties tested (Miranda, Izvor and Boema). The Miranda variety, tested alongside the Izvor and Boema varieties, in the experimental field at S.C.D.A. Brăila, on average over ten years (2011-2021), but also in official tests, proved to have a very high potential and stability of grain production and an increased resistance to drought and heat.
Keywords: climatic factors; wheat varieties; productivity elements